F18. PSYCHOPATHOLOGY AND SELF-CONCEPT IN A LONGITUDINAL COHORT OF CHILDREN WITH FAMILIAL HIGH RISK OF SCHIZOPHRENIA OR BIPOLAR DISORDER. (9th April 2019) - Ellersgaard, Ditte; Bruun, Julie E; Mors, Ole; Nordentoft, Merete; Thorup, Anne A E
Abstract: Background: For both schizophrenia and bipolar disorder, the single largest risk factor for developing the disorder is having a positive family history of the disorder. Therefore, children of parents with schizophrenia or bipolar disorder constitute relevant study populations for studying etiological pathways and early antecedents of these severe mental disorders. The aim of this study was to explore potential differences in trajectories of psychopathology and self-concept from age seven to age nine in children with familial high risk of schizophrenia or bipolar disorder and controls. Methods: A cohort of 522 children were recruited using the Danish nationwide registers. 202 children had at least one parent with a schizophrenia spectrum disorder, 120 had at least one parent with bipolar disorder and 200 were controls. Children in the control group were matched to children of parents with schizophrenia spectrum disorders on age, gender and municipality. Children in the control group could not have parents with schizophrenia spectrum disorders or bipolar disorder but were not excluded for any other reasons. At baseline, when the children were seven years old, they went through a comprehensive assessment including e.g. cognitive skills, motor functioning, psychopathology and self-concept. Psychopathology was examined with a variety of assessment tools including Child Behavior Checklist (CBCL). Self-concept was assessed with the 'I Think I Am' questionnaire, which measures five domains of self-concept. At the first wave of follow-up, at age nine the children's psychopathology and self-concept were once again assessed with the CBCL and the 'I Think I Am'. Results: The differences in psychopathological profiles and self-concept as well as differences in trajectories from age seven to age nine between the groups will be presented at the meeting. Discussion: The differences in trajectories of psychopathology and self-concept will be discussed in the context of possibilities for developing early intervention strategies towards children with familial risk of schizophrenia or bipolar disorder.